Identification of an analgesic lipopeptide produced by the probiotic Escherichia coli strain Nissle 1917. Issue 1 (December 2017) - Pérez-Berezo, Teresa; Pujo, Julien; Martin, Patricia; Faouder, Pauline; Galano, Jean-Marie; Guy, Alexandre; Knauf, Claude; Tabet, Jean; Tronnet, Sophie; Barreau, Frederick; Heuillet, Maud; Dietrich, Gilles; et al.
Abstract Administration of the probioticEscherichia coli strain Nissle 1917 (EcN) decreases visceral pain associated with irritable bowel syndrome. Mutation ofclbA, a gene involved in the biosynthesis of secondary metabolites, including colibactin, was previously shown to abrogate EcN probiotic activity. Here, we show that EcN, but not an isogenicclbA mutant, produces an analgesic lipopeptide. We characterize lipoamino acids and lipopeptides produced by EcN but not by the mutant by online liquid chromatography mass spectrometry. One of these lipopeptides, C12AsnGABAOH, is able to cross the epithelial barrier and to inhibit calcium flux induced by nociceptor activation in sensory neurons via the GABAB receptor. C12AsnGABAOH inhibits visceral hypersensitivity induced by nociceptor activation in mice. Thus, EcN produces a visceral analgesic, which could be the basis for the development of new visceral pain therapies. Escherichia coli Nissle is a probiotic that decreases visceral pain associated with irritable bowel syndrome. Here, the authors show that the microbe produces an analgesic lipopeptide, structurally related to GABA, that can cross the gut epithelial barrier and inhibits visceral hypersensitivity in mice.